Level of Public Satisfaction with Public Services: Case Study of the Dukong Village Office, Tanjung Pandan Subdistrict, Belitung Regency - Fachlovi, Venny Resti; Octavedha, Alfin Yuan (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The Dukong Village Office in Tanjung Pandan District, Belitung Regency, is one of the village administrations that provides services to the community. One of the issues frequently raised by some members of the community is that service hours sometimes do not align with the posted hours on the village office notice board, service staff take a long time to complete the necessary administrative tasks for the community, and they rarely listen to complaints or suggestions from the community. Additionally, the service facilities are considered inadequate, such as the limited seating in the waiting area. The level of community satisfaction with the services provided by the Mentawak Village Office is an interesting topic to study. The method used is a community satisfaction survey, with data collection techniques employing a questionnaire as the instrument. Based on the results and discussion, it can be concluded that the level of community satisfaction with the delivery of public services is already functioning well. This is evident from the 9 items/elements with an average score of 74.27, categorized as good. However, there are still shortcomings in three areas, namely service completion time, handling of complaints related to suggestions and input, and service facilities and infrastructure, which are categorized as poor. The author suggests that improvements or enhancements are needed in service delivery, particularly in terms of service completion time, handling of complaints related to suggestions and input, and service facilities and infrastructure.